Silica hairy nanoparticles: a promising material for self-assembling processes. Issue 41 (6th October 2021) - Tripaldi, Laura; Callone, Emanuela; D'Arienzo, Massimiliano; Dirè, Sandra; Giannini, Luca; Mascotto, Simone; Meyer, Andreas; Scotti, Roberto; Tadiello, Luciano; Di Credico, Barbara
Abstract : "Hairy" nanoparticles (HNPs), i.e. inorganic nanoparticles functionalized with polymer chains, are promising building blocks for the synthesis of advanced nanocomposite (NC) materials having several technological applications. Abstract : "Hairy" nanoparticles (HNPs), i.e. inorganic NPs functionalized with polymer chains, are promising building blocks for the synthesis of advanced nanocomposite (NC) materials having several technological applications. Recent evidence shows that HNPs self-organize in a variety of anisotropic structures, resulting in an improvement of the functional properties of the materials, in which are embedded. In this paper, we propose a three-step colloidal synthesis of spherical SiO2 -HNPs, with controlled particle morphology and surface chemistry. In detail, the SiO2 core, synthesized by a modified Stöber method, was first functionalized with a short-chain amino-silane, which acts as an anchor, and then covered by maleated polybutadiene (PB), a rubbery polymer having low glass transition temperature, rarely considered until now. An extensive investigation by a multi-technique analysis demonstrates that the synthesis of SiO2 -HNPs is simple, scalable, and potentially applicable to different kind of NPs and polymers. Morphological analysis shows the overall distribution of SiO2 -HNPs with a certain degree of spatial organization, suggesting that the polymer coating induces a modification of NP–NP interactions. The role of the surface PB brushes in influencing the special arrangement of SiO2 -HNPs was observed also in cis -1, 4-polybutadiene ( cis -PB), since the resulting NC exhibited the particle packing in "string-like" superstructures. This confirms the tendency of SiO2 -HNPs to self-assemble and create alternative structures in polymer NCs, which may impart them peculiar functional properties.